HEDGES DALAM BAHASA JEPANG - Claudia Herzegovina Putri (IZUMI, 2018)
Hedges is a restriction used by a person for protecting themselves or an effort of a face saving act. The hedges sign in Japanese has a uniqueness due to have a different pattern of sentences that differs from other language, that make us interested in examining the hedges sign in Japanese as a pragmatic study. The author collect the data using “simak-catat” method, then it was analyzed using descriptive method. The result is presented using informal method. The result is the hedges sign in Japanese is divided into four maxims. The hedges sign that meets the maxim of quantity is soukai, iyo iyo “eventually”, while the maxim of quality are tabun “perhaps", kamoshirenai “perhaps”, sou “seems”, dekirudarou “perhaps can”, the maxim of manner is ~tara ~omotteimasu “I suppose…if…”, and the last maxim is maxim of relenvance ~kedo “but, however…”. gb777gb777slot gacorgb777gb777GB777GB777slot gacorslot gacor